Dematin Regulates Thrombosis and Early Akt Activation - Ding, Yiwen. (Tufts University. Tisch Library., 2023)
Thesis (M.S.)--Tufts University, 2023-05.; Submitted to the Dept. of Pharmacology and Drug Development.; Advisor: Athar Chishti.; Keyword: Pharmacology.